Electroejaculation in the Chinchilla (Chinchilla lanigera): Effects of anesthesia on seminal characteristics - Busso, Juan Manuel (2005)
Repetitive electroejaculation is probably extremely stressful in conscious animals and could adversely affect fertility. The present study was designed to (a) evaluate the effects of anesthesia (40 mg ketamine/kg body weight, i.m.) on a method of electroejaculation used previously in conscious chinchillas (Chinchilla lanigera), and (b) determine the quality of the electroejaculated semen obtained under anesthesia. In Experiment 1 (8 animals), a 4 × 4 Latin square design was used to study the effects of anesthesia and ejaculatory voltage on semen collection, ejaculate volume, sperm concentration, motility, viability, response to the hypoosmotic swelling test (HOST), and acrosomal status. In Experiment 2 (12 animals), the effects of differing voltages and the number of stimuli on ejaculation by conscious or anesthetized males was determined. In both experiments, all the conscious animals ejaculated, but only 60% ejaculated under anesthesia and they required more stimuli and higher voltages to achieve ejaculation. Ejaculate volume was significantly lower in anesthetized (<5 μl) than in conscious animals (>40 μl), but sperm concentration was unaffected. None of the indices of sperm quality were affected by anesthesia. The techniques we have developed in anesthetized domestic chinchillas should be applicable to endangered chinchillas in the wild, and though the number of sperm available is reduced, there are still sufficient for assisted reproduction. © 2004 Elsevier Ltd. All rights reserved.